The limitations of locust preventive management faced with spatial uncertainty: exploration with a multi‐agent model. Issue 3 (18th October 2019) - Gay, Pierre‐Emmanuel; Lecoq, Michel; Piou, Cyril
Abstract: BACKGROUND: The spatial structure of locust outbreaks is a major aspect of preventive management that relies on where survey teams have to be sent if they are to react in time to any upsurge. The concentration of areas propitious to outbreaks has been documented for many species. Areas where preventive management fails to collect information because of insecurity or remoteness constitute other limits. We explored these conditions using a spatially explicit multi‐agent model representing a preventive management system. We simulated areas where field teams had limited or no access and areas where the probability of initial outbreaks was concentrated in hotspots. RESULTS: A strong effort by the budget holder to maintain funding over time might be cancelled out with 5% of a territory having limited access. The larger the area of no access, the worse the proportion of plague years. Multiple no access areas generated more plagues than only one no access area of an equivalent size because more fronts must be controlled. Concentrating outbreaks in hotspots increased the probability of plagues. One hotspot alone was easier to control than several same‐sized hotspots. The period of the budget holder's cyclical behaviour between awareness and reduction in funding was longer with one hotspot than with several. CONCLUSION: These results highlight the need to consider the spatial conditions and accessibility of locust species when planning the sustainability of management systems. Despite significant budgets to set in place a preventive management system, cyclical locust outbreaks may be related to these spatial conditions. © 2019 Society of Chemical Industry Abstract : A multi‐agent model simulating cyclic locust plagues showed that with spatial uncertainty, plagues are more frequent and the time between budget holder awareness and a reduction in funding is shorter.